Transplantation of melanocyte stem cells in vitiliginous skin - Yohanes Widodo Wirohadidjojo; Flandiana Yogianti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
Depigmentation in vitiligo occurs as a result of progressive loss of functioning epidermal melanocytes, and currently various modalities have been developed to re-functioning these cells. However, in area with poor melanocytes reservoir, such as old-persistent lesions or lesions on bony prominence, the modalities are hardly to achieve repigmentation. Since spontaneous repigmentation of vitiliginous skins begin mostly in follicular areas, reactivation of melanocyte precursors along the outer root sheath of hair follicle is expected to have better on this pigmentation. Melanocyte precursor came from melanocyte stem cells that originally located on bulge area of hair follicles. The latest surgical intervention in vitiligo is transplantation of melanocyte stem cells. Clinical experiments indicated that the transplantation can be performed either by transplantation of extracted follicular units or single cell suspension harvested from this area. By single cell suspension treatment, a 50 cm2 of vitiliginous skin can be handled by 15 autologous hair follicular units. These procedures are easy and can be performed by any dermatologist especially who has been trained in dermatologic surgery as well as in cellular based therapies.